Wear effects between polymethyl methacrylate occlusal splints and opposing dentin surfaces during bruxism mimicking events - Prangtip Potewiratnanond; Cholakorn Ekrojanakul; Tatcharee Harikul; Rapatporn Kositvanich (Nature Publishing Group, 2023)
Abstract Objectives To compare the surface wear rate between polymethyl methacrylate (PMMA)-based occlusal splints and opposing dentin-exposed teeth in bruxism simulating models. Materials and methods PMMA-based occlusal splints and extracted premolars were tested on a chewing stimulator at 30,000 or 60,000 cycles. Dentin wear was measured under a stereomicroscope and PMMA wear was determined with an optical profilometer. In addition, wear surface topography was assessed and quantified by scanning electron microscopy (SEM). Results Wear rate of PMMA was significantly greater (11 times) than that of dentin specimens at 60,000 cycles, though these findings were not observed at 30,000 cycles. When comparing wear rates within each group at different duration cycles, PMMA surfaces exhibited an average wear rate 1.4 times higher with high duration cycles, while dentin surfaces displayed a marginal decrease in wear. In SEM micrographs, PMMA surfaces displayed more wear abrasion lines with higher duration cycles. However, dentin surfaces did not exhibit major differences between low and high duration cycles. Conclusion Wear rate on PMMA-based occlusal splints remarkably increases upon high chewing cycles mimicking bruxism comparing with the rate on dentin. Hence, it is reasonable for bruxing patients to wear single-arch PMMA-based occlusal splints to protect opposing dentin-exposed teeth.